The role of the family in determining a child's educational outcomes - Kola, Sameeha (School of Economics, 2015)
Despite the government’s attempts to remedy the inequities of apartheid, there are large racial differences in educational outcomes, with whites performing substantially better than non-whites. In understanding these differences most studies have emphasised the role of school quality, without adequate emphasis on the role of the family. This study has investigated the role of the family in determining educational outcomes, and further how this is different for non-whites and whites. A holistic model of education was used which investigates the role of the family, while controlling for the effect of individual and school level characteristics that impact outcomes. Test scores from a literacy and numeracy evaluation were regressed on family level variables (family structure, parental involvement and socio-economic status), school quality variables and measures of individual ability and effort. The results of this study highlight that parental involvement and socio-economic status play an important role in the educational outcomes of both non-whites and whites, even after controlling for differences in school quality and individual ability and effort. It is not clear that family structure on its own accounts for variations in educational outcomes. Rather it is suggested it operates indirectly through impacting the parental involvement and financial resources available for education. Socio-economic status seems to play a much larger role in explaining the variations in outcomes of white students as compared to non-whites, suggesting a threshold level of socio-economic status above which differences matter more. Parental involvement levels are uniformly high among whites, and therefore does not serve to explain variations in educational outcomes amongst whites. Parental involvement does however have a role in accounting for variations between whites and non-whites and also amongst non-whites. The implications of this study highlight the need to encourage parental involvement amongst non-white families, as a means to improve educational outcomes. The lack of parental involvement often stems from a lack of parental education, impacting the ability to support the educational progress of their children. Programs that enable and equip non-white parents to understand how the educational system works, and how best to assist their children in school, would have lasting benefits by improving the long term prospects of their children.